Analyzing the Health Status of Slum Dwellers: An Evidence of Lahore, Pakistan - Muhammad Hassan Safdar, Riaz Ahmed, Najaf Hussain, Muhammad Arslan Safdar, Tausif Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Miserable status of health and public health is one of the major problems of more than 1 billion people living in slums across the world. Most of the governments, do not pay due attention. Purpose: Current study is especially devised to highlight the major problems of slum population in relation with health and public health so that better policy measures might be suggested. The second most populous city of Pakistan is Lahore and it is the home of about 27 million people, slums area of Lahore were chosen as population. Methodology: Through stratified sampling technique 250 households from ten slums were chosen as a sample. Inferential and descriptive statistical techniques have been used study in hand. The logistic regression model has been used to analyze the impact of important socio-economic variables on the health status of the family. Results: From descriptive analysis, we know that about 73 percent of the slum residents have no access to even basic health facilities, 32 percent of the slum children are not immunized, 72 percent of the slum women give birth to children without any proper assistance and 56 percent do not receive antenatal check – ups during pregnancy. Further, about 66 percent of the dwellers have no access to safe drinking water while majority face unhygienic and poor solid waste management status. Conclusion: The results of regression model shows that per capita income, education level of the family head, availability of safe drinking water and employment status of the family have positive while smoking and drinking leave negative impact on the health status of the dwellers. The findings address the authorities concerned to take holistic and practical measures for betterment of human development. Keywords: Slums, Antenatal Care, Basic Health Facilities, Safe Water, Immunization, Solid Waste Management